Laboratorial diagnosis of Cushing's syndrome. - Alves, Marta (2010)
Cushing's syndrome is a diagnostic challenging endocrinous entity. Many laboratorial examinations are available for the study of these patients. Available examinations are not absolutely trustworthy for its diagnosis, so that, very often, it is necessary to conjúgate informations from different laboratory tests. In this revision one exposes the current evidence and the suggestions of different authors in the laboratorial diagnosis of Cushing's syndrome and the differential diagnosis in patients with biochemical confirmed diagnosis.